Studies on the preparation of chapatti and biscuit supplemented with potato flour - Khaliduzzaman, M; Shams-Ud-Din, M; Islam, MN (Journal of the Bangladesh Agricultural University, 2010)
The present study was concerned with the preparation of potato flour with various treatments and to formulate the chapatti and biscuit incorporating potato flours were prepared by treating the raw potato slices as blanched, blanched plus potassium meta-bisulphite (KMS) treatment and one as control. Various substitution levels from 15 % to 30 % of potato flour was used in the formulations of chapatti and biscuit in conjunction with wheat flour. Chapatti and biscuit prepared with either blanched or blanched plus KMS treated sample of potato flour had very good physical and baking quality. And chapatti prepared with 20% potato flour and biscuit containing 25 % had the most suitable baking properties among other proportions. The statistical analysis of sensory evaluation data indicated that the baked products prepared with potato flour from blanched plus KMS-treated samples ranked very well and were more acceptable than those made from blanched sample. Keywords: Potato flour; Drying; Chapatti; Biscuit DOI: 10.3329/jbau.v8i1.6413 J. Bangladesh Agril. Univ. 8(1): 153-160, 2010